2020
DOI: 10.1002/joc.6790
|View full text |Cite
|
Sign up to set email alerts
|

Elevation‐dependent precipitation response to El Niño‐Southern oscillation revealed in headwater basins of the US central Rocky Mountains

Abstract: We used nonparametric analyses of gridded precipitation data from the Parameter‐Elevation Relationships on Independent Slopes Model (PRISM) to examine teleconnections between the El Niño‐Southern Oscillation (ENSO) and elevation‐related precipitation variability from 1950 to 2016 over the Snake‐Salt, Wind‐Bighorn, Green, and Platte basins, which span the North American continental divide. Our analyses parse data into three‐month‐long meteorological seasons and use the Japan Meteorological Agency (JMA) index to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The combined effects could have favored the unusually high δ 18 O carb at HL by positively shifting the isotope values of mean annual precipitation and HL's water. Alternatively, the reversed hydrologic response of Hidden Lake could indicate antiphased hydroclimate changes in the southern Rocky Mountains between high and low elevations, which is consistent with modern responses to the El Niño-Southern Oscillation (Preece et al, 2021). The active dune fields in east-central Wyoming, however, could confound a simple interpretation of the elevational and seasonally antiphased hydrologic changes, although their activity may depend on soil moisture derived from winter snow (Stokes and Gaylord, 1993).…”
Section: Evidence Of the 42 Ka Drought In The Southern Rocky Mountainsmentioning
confidence: 74%
“…The combined effects could have favored the unusually high δ 18 O carb at HL by positively shifting the isotope values of mean annual precipitation and HL's water. Alternatively, the reversed hydrologic response of Hidden Lake could indicate antiphased hydroclimate changes in the southern Rocky Mountains between high and low elevations, which is consistent with modern responses to the El Niño-Southern Oscillation (Preece et al, 2021). The active dune fields in east-central Wyoming, however, could confound a simple interpretation of the elevational and seasonally antiphased hydrologic changes, although their activity may depend on soil moisture derived from winter snow (Stokes and Gaylord, 1993).…”
Section: Evidence Of the 42 Ka Drought In The Southern Rocky Mountainsmentioning
confidence: 74%
“…Low winter snow can create favorable surface-energy conditions for strong summer convective precipitation (Zhu et al 2005). Alternatively, the reversed hydrologic response of Hidden Lake could indicate antiphased hydroclimate changes in the southern Rocky Mountains between high and low elevations, which is consistent with modern responses to the El Niño-Southern Oscillation (Preece et al, 2020). The active dune fields in east-central Wyoming, however, confound a simple interpretation of the elevational and seasonally antiphased hydrologic changes.…”
Section: Brunellementioning
confidence: 80%
“…These results differ from those of Praeg et al (2020), who studied the elevation gradient of pastures less than 2000 m and found that soil pH decreased with increasing elevation. The reason for this difference may be that atmospheric circulation influences precipitation so that it gradually increases with elevation at lower elevations (Yao et al, 2016;Li et al, 2017;Preece et al, 2021) and then shows a decreasing trend, probably due to the peculiarity of the study region which has a difference of about 2,700 m between high and low elevations. However, the regions above 3,800 m are mainly located in the northwest of Maqu County, where some literatures indicate that the region is vulnerable to climatic effects (Wu et al, 2019;Yang et al, 2021).…”
Section: Influence Of Topography On Soil Water-saltmentioning
confidence: 93%